Author Response: Association of Fecal and Plasma Levels of Short-Chain Fatty Acids With Gut Microbiota and Clinical Severity in Patients With Parkinson Disease. (30th August 2022) - Lin, Chin-Hsien; Chen, Szu-Ju; Kuo, Ching-Hua
Abstract : We are grateful for the comment on our study. 1 We are pleased to know that short-chain fatty acids (SCFAs), especially butyrate, in the intestine could stimulate the colonization of curli-producing Escherichia coli . Curli are functional amyloids produced by gut microbes and act as cross–beta-sheet amyloid polymers to assist bacterial cells in binding to one another to form biofilm. 2 Curli participate in the intracellular self-assembly process of pathologic human amyloids, including α-synuclein, leading to proteopathy and the promotion of intestinal inflammation through toll-like receptors (TLRs), or mapranosis. 3 A study implanting curli-producing E. coli in germ-free α-synuclein-overexpressing mice resulted in α-synuclein aggregations and neuroinflammation, with an increased expression of tumor necrosis factor alpha (TNFα). 4 This Parkinson disease (PD)–like neuropathology was reversed in mice colonized with a curli-deficient E. coli strain, supporting that gut microbial amyloids can exacerbate gut and neuropathology of PD. 4 These observations are compatible with recent evidence that intestinal inflammation promotes PD neuropathology through activating TLRs and TNFα-mediated neuroinflammation. 5 Furthermore, there are many members of the microbiome capable of producing functional amyloids, including Klebsiella species, for which abundance has a positive correlation between the plasma butyrate levels in patients with PD in our study. 1 SCFAs may play a pivotal role in the gut-brain communication of the PD process.